Organizational behavior and management - Konopaske, Robert; Ivancevich, John M.; Matteson, Michael T. (New York, NY : McGrawHill, 2023)
'Revising and updating this textbook is truly a labor of love. In completing this twelfth edition of Organizational Behavior and Management, we reviewed the most current theories, research, and organizational applications for possible inclusion. We retained the classic, influential, and long-standing work in organizational behavior. Chapter by chapter, we made a concerted effort to add several more company and other real-world examples (e.g., COVID-19's impact on organizations and managers) to make the content more relevant and interesting for students. Our own teaching of organizational behavior and many excellent suggestions from the reviewers of the previous edition were factored into each phase of the revision'--
Includes bibliographical references and index.
Keywords: Organizational behavior